Control Interno A Los Procesos De Pagos En La Dirección De Talento Humano De La Universidad Técnica De Babahoyo - Gavilanez Acosta, Orlando Ronaldo (2018)
The present case study conducted at the Technical University of Babahoyo, in order to detect the different factors that cause the delay of payments to staff and thus determine the shortcomings within the Human Talent Directorate. The aforementioned department is one of the most relevant areas within any institution that prioritizes its staff, because it plans, organizes, trains, seeks the comfort, health and safety of its employees; The control carried out in this area is fundamental for the processes to follow their normal course of action without any inconvenience or delay.